2013
DOI: 10.2105/ajph.2012.301121
|View full text |Cite
|
Sign up to set email alerts
|

A Sexual Risk and Stress Reduction Intervention Designed for HIV-Positive Bisexual African American Men With Childhood Sexual Abuse Histories

Abstract: Objectives. HIV transmission risk is high among men who have sex with men and women (MSMW), and it is further heightened by a history of childhood sexual abuse (CSA) and current traumatic stress or depression. Yet, traumatic stress is rarely addressed in HIV interventions. We tested a stress-focused sexual risk reduction intervention for African American MSMW with CSA histories. Methods. This randomized controlled trial compared a stress-focused sexual risk reduction intervention with a general health promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 78 publications
0
61
0
Order By: Relevance
“…This type of sexual trauma is strongly linked to HIV risk (Benoit & Downing, 2013; Eaton et al, 2013; Williams, Kisler, Glover, & Sciolla, 2011; Williams et al, 2013) and elevated levels of prior experience with sexual abuse have been observed among MSMW (Eaton et al, 2013; Kim et al, 2012; Williams et al, 2011; Williams et al, 2013). Finally, there is evidence that sexual trauma contributes to mental illness (Ford, Elhai, Connor, & Frueh, 2010; Johnson, Cottler, Abdallah, & O’Leary, 2011; Sartor et al, 2012), substance use (Briere, Kaltman & Green, 2008; Huang et al, 2011; Skeer, McCormick, Normand, Buka, & Gilman, 2009) and HIV-related sexual risk (Catania et al, 2008; Haydon, Hussey & Halpern, 2011; Huang et al, 2011; Medrano & Hatch, 2005; Senn & Carey, 2010; Wilson & Widom, 2009) that cluster in criminal justice involved populations, as well as contribute to criminal justice involvement (Messina & Grella, 2006; Senn, Carey & Vanable, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This type of sexual trauma is strongly linked to HIV risk (Benoit & Downing, 2013; Eaton et al, 2013; Williams, Kisler, Glover, & Sciolla, 2011; Williams et al, 2013) and elevated levels of prior experience with sexual abuse have been observed among MSMW (Eaton et al, 2013; Kim et al, 2012; Williams et al, 2011; Williams et al, 2013). Finally, there is evidence that sexual trauma contributes to mental illness (Ford, Elhai, Connor, & Frueh, 2010; Johnson, Cottler, Abdallah, & O’Leary, 2011; Sartor et al, 2012), substance use (Briere, Kaltman & Green, 2008; Huang et al, 2011; Skeer, McCormick, Normand, Buka, & Gilman, 2009) and HIV-related sexual risk (Catania et al, 2008; Haydon, Hussey & Halpern, 2011; Huang et al, 2011; Medrano & Hatch, 2005; Senn & Carey, 2010; Wilson & Widom, 2009) that cluster in criminal justice involved populations, as well as contribute to criminal justice involvement (Messina & Grella, 2006; Senn, Carey & Vanable, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite what is known about the elevated risks among this group and their distinct prevention needs, few interventions have been rigorously evaluated and demonstrated to be effective for reducing risk among black MSMW (Fernandez et al, 2016;Harawa et al, 2013;Williams et al, 2013). We undertook a study to better understand the sexual and HIV risk behaviors of black MSMW.…”
mentioning
confidence: 99%
“…MAALES, which has been described elsewhere [2,4], involves didactic and skill-building components addressing HIV/STI knowledge, sexual negotiation, risk reduction (including proper condom use and reducing riskly sexual behaviors related to substance use), and HIV and STI testing and treatment. Identifying holistic health issues and goal setting, particularly related to smoking and diet, was also addressed and encouraged.…”
Section: Mile Interventionmentioning
confidence: 99%
“…HIV infection rates among Black men who have sex with both men and women (MSMW) are disproportionately high compared with those of MSMW of all other races and ethnicities [1], with very few HIV prevention intervention trials for Black MSMW [2][3][4]. Because Black MSMW are less likely to participate in gay communities and less likely to disclose same sex contact than other MSMW, Black MSMW are unlikely to respond to interventions targeting gay men [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%